Analysis of Iodine Content in Table Salt - Wulandari, Eka Ratri Noor; Rosyida, Novita (UI Scholars Hub, 2017)
Iodine is an essential nutrient for the human body. It is required by the thyroid gland for producing the thyroxine hormone. Human body lacks the ability to self-produce iodine. Some sources of iodine in food such as seafood, milk, egg, fruits, and vegetables can be consumed to fulfill the daily needs. Table salt is one of the sources of iodine that is routinely consumed. According to SNI No. 3556:2010, table salt must be fortified with 30–80 ppm of potassium iodate. Lack of iodine intake results in a disorder known as the iodine deficiency disorder, which is generally manifested as mumps. This study analyzed the content of iodate in table salt based on the formation of the blue I2–starch complex. Several optimum conditions were used for this measurement, such as the maximum wavelength, the type and concentration of acid, and the stability time of the complex. Based on the analysis of commercial table salt samples, the results showed that only 50% of our samples contained an appropriate amount of iodine, whereas the remaining samples contained lower or almost no iodine content.